Seeing Red : China's Uncompromising Takeover of Hong Kong - Allen, Jamie (Singapore B-H Asia, 1997)
Seeing Red tracks the progress of China's hard-nosed takeover strategy since the signing of the Sino-British Joint Declaration in December 1984. It examines the Basic Law from the perspective of China's political imperatives, and describes the steady advance of mainland Chinese business interests in the colony. He finds that Hong Kong's reunification with China has more to do with a process of recolonization than decolonization.
Include Maps, Appendix, Notes and Index.
China's Uncompromising Takeover of Hong Kong
Keywords: China--Hong Kong -- Economic history -- China -- Politics and government -- Transfer of Hong Kong's Sovereignty (1997) -- Commercial policy